Pengaruh Citra Merek (Brand Image), Kualitas Produk terhadap Keputusan Pembelian Semen Tiga Roda: Studi pada Toko Bangunan Kecamatan Sukasada - Putu Julia Dewi; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
The purpose of this study is to analyze the influence of brand image, product quality on purchasing decisions of three-wheeled cement studies at building stores in Sukasada District, both partially and simultaneously. This study uses a quantitative approach with a causal research type. The population in this study were consumers who had purchased three-wheeled cement, totaling 422 consumers. The sampling technique used was proportional random sampling, with a sample size of 81 respondents. The type of data used is quantitative, with data sources derived from primary data. Data collection was carried out through questionnaires, observations, and documentation. To analyze the data, this study used multiple linear regression analysis techniques. Hypothesis testing was carried out partially using the t-test and simultaneously using the F-test. The research results showed that (1) brand image has a positive and significant influence on the decision to purchase three-wheeled cement at the Sukasada District building store, (2) product quality has a positive and significant influence on the decision to purchase three-wheeled cement at the Sukasada District building store, and (3) simultaneously, brand image and product quality together have a positive and significant influence on the decision to purchase three-wheeled cement at the Sukasada District building store.